PENGARUH PENDAPATAN DAN PENJUALAN TERHADAP JENJANG KARIR DI TOKO ANEKA SUMBER MEDAN - Florencia; Dewi Anggraini (Universitas HKBP Nommensen, 2025)
This study aims to analyze the influence of income and sales on employee career advancement in the glassware sales division at Toko Aneka Sumber Medan. The population in this study consists of all employees in the glassware sales division, with a total sample of 30 respondents. The research employs a descriptive quantitative approach using multiple linear regression analysis. The results show that: 1) Income has a positive and significant effect on employee career advancement, 2) Sales performance has a positive and significant effect on employee career advancement, and 3) Income and sales performance simultaneously have a positive and significant effect on employee career advancement at Toko Aneka Sumber Medan.